2022
DOI: 10.1080/21655979.2022.2053796
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0000081 promotes the function of gastric cancer through sponging hsa-miR-423-5p to influence 3-phosphoinositide-dependent kinase 1 expression

Abstract: Gastric cancer (GC) is one of the most common malignancies in the world, and effective therapeutic targets need to be identified for this type of cancer. In this study, circular RNA (circRNA) microarray analysis was utilized to screen differentially expressed circRNA in GC. Using quantitative reverse transcription polymerase chain reaction (qRT-PCR), hsa_circ_0000081 (circRNA-0000081) expression was found to be up-regulated in tissues and cells and was negative correlated with patients’ survival time. RNase R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…CircRNA microarray was performed to investigate potential key circRNA in GC (Kang Chen Biotech, Shanghai, China) as we covered in our previous article [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…CircRNA microarray was performed to investigate potential key circRNA in GC (Kang Chen Biotech, Shanghai, China) as we covered in our previous article [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…miR-423 is also sponged by other lncRNAs in other cell types, such as LINC00680 in oesophageal squamous cell carcinoma cells [ 46 ] and AFAP1-AS1 in nasopharyngeal carcinoma cells [ 47 ]. A recent report showed that circRNA-0000081 maintains the levels of PDPK1 (a target of miR-423) in gastric cancer cells via miR-423 sponging, thereby affecting cell proliferation, migration, and invasion potential [ 48 ]. In the present study, we discovered a new signaling pathway, the NORHA /miR-423/ SMAD7 pathway, that contributes to FA and GC apoptosis and enriches the ceRNA network of the NORHA -miRNAs in GCs.…”
Section: Discussionmentioning
confidence: 99%
“…All the aforementioned cell lines were meticulously nurtured in RPMI 1640 medium (Thermo Fisher Scientific Inc, USA), which was supplemented with 10% fetal bovine serum (FBS, Thermo Fisher Scientific Inc, USA) and 1% penicillin-streptomycin (comprising 10,000 U/mL penicillin + 10,000 µg/mL streptomycin, Thermo Fisher Scientific Inc, USA), which we used in the refer to this medium here as complete medium. The cultivation of these cells transpired under precisely controlled conditions, specifically at a temperature of 37°C , within an environment enriched with 5% CO2, within a dedicated carbon dioxide cell incubator [14].…”
Section: Cell Linesmentioning
confidence: 99%